The Effective Executive - Drucker, Peter F. (Peter Ferdinand), 1909-2005 (New York Harper Business, 2006)
[The author] identifies five practices essential to business effectiveness that can, and must, be learned: Managing time; Choosing what to contribute to the organization; Knowing where and how to mobilize strength for best effect; Setting the right priorities; Knitting all of them together with effective decision-making
Include Index
Keywords: Executives -- United States -- Decision making -- Industrial management